Limits to post‐fire vegetation recovery under climate change. (16th September 2021) - Nolan, Rachael H.; Collins, Luke; Leigh, Andy; Ooi, Mark K.J.; Curran, Timothy J.; Fairman, Thomas A.; Resco de Dios, Víctor; Bradstock, Ross
Abstract: Record‐breaking fire seasons in many regions across the globe raise important questions about plant community responses to shifting fire regimes (i.e., changing fire frequency, severity and seasonality). Here, we examine the impacts of climate‐driven shifts in fire regimes on vegetation communities, and likely responses to fire coinciding with severe drought, heatwaves and/or insect outbreaks. We present scenario‐based conceptual models on how overlapping disturbance events and shifting fire regimes interact differently to limit post‐fire resprouting and recruitment capacity. We demonstrate that, although many communities will remain resilient to changing fire regimes in the short‐term, longer‐term changes to vegetation structure, demography and species composition are likely, with a range of subsequent effects on ecosystem function. Resprouting species are likely to be most resilient to changing fire regimes. However, even these species are susceptible if exposed to repeated short‐interval fire in combination with other stressors. Post‐fire recruitment is highly vulnerable to increased fire frequency, particularly as climatic limitations on propagule availability intensify. Prediction of community responses to fire under climate change will be greatly improved by addressing knowledge gaps on how overlapping disturbances and climate change‐induced shifts in fire regime affect post‐fire resprouting, recruitment, growth rates, and species‐level adaptation capacity. Abstract : Although many vegetation communities will remain resilient to changing fire regimes under climate change in the short‐term, longer‐term changes to vegetation structure, demography and species composition are likely, with subsequent impacts to ecosystem function. Resilience will depend on species‐specific adaptations to fire, with resprouting species likely to be most resilient.